Draft Genome Sequence of a Multidrug-Resistant Pseudomonas aeruginosa Strain Isolated from a Patient with a Urinary Tract Infection in Khartoum, Sudan - Hussain, Mohamed (Genome Announc, 2017)
Pseudomonas aeruginosa infection is difficult to treat due to the presence of antibiotic resistance determinants. Here, we report the genome sequence of a multidrug-resistant P. aeruginosa strain isolated from a patient with a urinary tract infection in 2015.